Adaptive Sliding Mode Control for Magnetic levitation system - Al-Samarraie, Shibly Ahmed; Midhat, Bashar Fateh; Al-Deen, Rand Ahmed Bahaa (Al-Nahrain Journal for Engineering Sciences, 2018)
In this paper, an Adaptive Sliding Mode Controller (ASMC) is designed and applied for a magnetic levitation system (Maglev) where a steel ball is desired to be stabilized at a desired position with existence of uncertainty in system model. Additionally, a sliding mode differentiator (SMD) is used for estimating the ball velocity since it’s needed for the controller to work properly. The designed controller and differentiator are applied practically to an experimental laboratory size magnetic levitation system and the results were plotted to show the behavior of the system under the effect of the designed controller. The experimental results reveal clearly the effectiveness and ability of the suggested controller in forcing the steel ball to follow various desired position.